The Development of Conceptual Change Theory-Based E-Modules Equipped with Conceptual Change Texts on the Solar System Topics - Yenita Yenita; Syuhendri Syuhendri; Sardianto Markos Siahaan (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop a set of e-module teaching materials equipped with conceptual change text based on conceptual change theory on the Solar System materials. The research method used was Educational Design Research (EDR) with the Plomp model. The research consisted of three stages, namely the preliminary study, design development and product testing. At the initial stage, an analysis of competencies, essential materials, and misconceptions experienced by students in the Solar System material was carried out. There were major misconceptions such as the Sun as the biggest star, the motion of the planets that are always the same, the phases of the moon, revolution and rotation of the earth, Kepler's Laws II and III, solar eclipses, and Newton's gravity that occurs between the earth and the moon as well as the earth and the sun. These findings are the basis for developing the e-module. Based on the validation and practicality tests, the validation level was obtained at 3.85 which means very valid category and practicality at 93% means very practical category. Therefore, it can be concluded that the developed e-module teaching materials based on the conceptual change on the Solar System topics are valid and practical.